Bible translation as mediator of Hebrew impact on target languages: the Estonian bible translation by Johannes Gutslaff - Ross, Kristiina (Nordisk judaistik, 2000)
The full version of the Bible was first published in Estonian in 1739. In comparison with the neighbouring Protestant countries this is a very late date. However, serious attempts to translate the Bible into Estonian were made already in the 17th century. There are two manuscripts from the 17th century which contain translations of the Old Testament. The older manuscript dating from the middle of the century has been - unlike e.g. the Finnish Bible which had been translated from Luther’s German version - translated directly from Hebrew, by Johannes Gutslaff. Also the 1739 Estonian version was translated directly from the Hebrew version. As is widely known, Luther was of the opinion that a translator should not follow the structure of the source language&&instead, he must use the fluent and pure target language. The Estonian translations followed strictly the Hebrew version, which resulted in the fact that still today, Estonian phraseology has Hebrew influence.